SUBSTANTIATION OF THE CONCEPT OF AN ECONOMIC AND MATHEMATICAL MODEL FOR ASSESSING INFORMATION RISKS OF AN ORGANIZATION - I. Mandritsa; T. Minkina; V. Kopytov; T. Doroshevskya (Вестник Северо-Кавказского федерального университета)
In article we propose the formalization of models and to describe the process of analysis and measurement of information risks for IT-systems of the organization. The proposed model complies with international standards and recommendations for non-profit organizations. The factors of the conceptual model, the significance and correlation of the relationship of factors, which was first carried out for commercial and non-commercial (budgetary) organizations to describe the economic result of their business process, are described. The model takes into account solutions used in well-known and recommended world standards and methods of risk analysis, and provides an assessment of the effectiveness of these information security solutions.